A study of carrier pulse width modulation for single phase 5-levels cascaded inverter - Nguyễn Phước Lộc; Bùi Thanh Hiếu; Võ Quốc Thái; Đào Thị Bé Dung; Nguyễn Văn Nhờ (Journal of Technical Education Science, 2021)
This paper studies and compares carrier-based pulse width modulation (CPWM) techniques. In which, two techniques of co-phase carrier modulation (PD PWM) and phase shift carrier modulation (PS PWM) are applied on a 5-levels cascaded single-phase inverter (CHB Inverter). The quality of the converter is evaluated based on the total harmonic distortion (THD%) output current and voltage of the inverter to be investigated, analyzed, evaluated, and compared. The modeling and simulation for the 5-levles cascaded single-phase inverter are done by MATLAB/SIMULINK software and the simulation results will be experimentally verified on the 5-levels Cascaded inverter hardware model built according to flexible module form and controlled by DSP 28379D microcontroller.